Road Rage Behaviour In Movie Unhinged Directed By Derrick Borte Through Psychoanalytic Approaches - Destrianaputri Ramadita (CV. Kalimasada Group Profesional, 2023)
Road rage is a phenomenon that involves the connection between human anger and driving performance. This study aims to discover about how road rage is being portrayed in movie Unhinged and to know the interconnection between characters based on their background and motives. This research uses the psychoanalysis theory of Freud in